Market Design for a High-Renewables Electricity System (Energies, 2020)
The book provides assessments and evaluations of emerging trends in the electricity markets, with a focus on high-renewables electricity systems. Specifically, various issues are examined, such as wind and solar energy, interconnection, smart meters, smart grids of the future (including their social implications), and peer-to-peer (P2P) electricity trading, which is closely connected to the principle of a sharing economy. The book also contemplates how the market design for a high-renewables electricity system would be different from the classical post-liberalization market design.